Computed tomography findings of acute gastric volvulus - Millet, Ingrid; Orliac, Celine; Alili, Chakib; Guillon, Françoise; Taourel, Patrice (European radiology, 2014)
Purpose To assess the diagnostic performance of CT signs of gastric volvulus in both confirmed cases and control subjects. Materials and methods We retrospectively reviewed CT findings in 10 patients with surgically confirmed acute gastric volvulus and 20 control subjects with gastric distension. Two radiologists independently evaluated CT images for risk factors of gastric volvulus, direct findings of gastric volvulus by assessing gastric dilatation, the presence of an antropyloric transition point, the respective position of the different stomach segments and of the greater and lesser curvatures, stenosis of the gastric segments through the oesophageal hiatus and for findings of gastric ischemia. The sensitivity and specificity of each finding were calculated. Results The most sensitive direct signs of gastric volvulus were an antropyloric transition point without any abnormality at the transition zone and the antrum at the same level or higher than the fundus. The presence of both these two findings as diagnostic criteria of gastric volvulus had 100 % sensitivity and specificity for the diagnosis of gastric volvulus. There was no association between CT signs of ischemia and final bowel ischemia at pathology. Conclusion CT is both highly sensitive and specific for diagnosing acute gastric volvulus. Key Points • CT is highly reliable for diagnosing acute gastric volvulus with two findings. • The two signs are gastropyloric transition zone and abnormal location of the antrum. • This allows fast surgical management of this emergency.